Life experiences after kidney transplantation in adolescents: A qualitative meta-synthesis - Wenjuan Zhang; Jiaqi Wang; Ziyu Sun; Yuhong Wu (PLoS ONE, 2025)
Purpose To systematically evaluate the life experience of adolescents after kidney transplantation. Methods We use computer search Web of Science, PubMed, Cochrane Library, Embase, EBSCO, CNKI, Wanfang, VIP database, search database to October 2024, screening after kidney transplant adolescents life experience of qualitative study. We used the Australian Joanna Briggs Institute Critical Appraisal Checklist for Qualitative Research to quality evaluation, and using the thematic analysis method to integrate the results. Results 7 articles were included, and 31 research results were integrated into 8 new categories and combined results are 3 integration results: complex emotional experience; eager for multifaceted support; self-adjustment. Conclusion Nursing staff should pay attention to the psychological experience and needs of adolescents, to eliminate their stigma, to promote positive cognition, and to improve their quality of life.